Production and optimization of halophilic lipase through solid state fermentation by halophilic bacteria - Nur Amirah Mahfod (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Halophilic lipases are hydrolytic enzymes that are stable and it catalyze the cleavage of ester bonds in triglycerides to free fatty acids, mono and diacylglycerols and glycerol. Therefore, it makes the halophilic lipases a valuable catalyst for many industrial applications. The tolerance of lipase enzyme produced by halophilic bacteria can be exploited to function under extreme conditions as in the presence of organic solvents and high in temperature and such salt content. This research draws attention to industries for ways to improve production of lipases by discovering new high enzyme producing halophilic bacteria together with optimizing the production condition with a few parameters such as type of carbon, nitrogen and oil inducers source, moisture content, temperature, pH and NaCl concentration. Twenty-one bacteria strains were obtained from stock culture in Laboratory of Bioprocess Engineering School. Screening by tributyrin agar was carried out to make sure the strains are all lipolytic and to find the potential highest enzyme producing microorganism. After screening process, the chosen 3 best strains were proceeding into Solid State Fermentation (SSF) process and the highest producing halophilic lipase microorganism was selected (SWJ 1) for optimization steps. Optimization process were conducted using One Factor at A Time (OFAT) method and Response Surface Methodology (RSM) in conjunction with Central Composite Design (CCD). The factors were carbon source, nitrogen source, oil inducers, moisture content, temperature, pH and NaCl concentration. Factors that induce the best halophilic lipase were yeast extract (carbon source) , casein hydrolysed (nitrogen source), olive oil ( oil inducers) with a 90% (v/w) moisture content , pH 7 and 10% of NaCl concentration under 45 C temperature. Other than that, the optimum halophilic lipase production was obtained at 10.38% (w/w) of yeast extract, 0.44% (w/w) of casein hydrolysed and 7.38% (v/w) of olive oil. This research has potential to be used in industry at the same time helps to reduce pollution by converting waste materials into valueble product.